3m+(m+1)=6m+1

Simple and best practice solution for 3m+(m+1)=6m+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+(m+1)=6m+1 equation:


Simplifying
3m + (m + 1) = 6m + 1

Reorder the terms:
3m + (1 + m) = 6m + 1

Remove parenthesis around (1 + m)
3m + 1 + m = 6m + 1

Reorder the terms:
1 + 3m + m = 6m + 1

Combine like terms: 3m + m = 4m
1 + 4m = 6m + 1

Reorder the terms:
1 + 4m = 1 + 6m

Add '-1' to each side of the equation.
1 + -1 + 4m = 1 + -1 + 6m

Combine like terms: 1 + -1 = 0
0 + 4m = 1 + -1 + 6m
4m = 1 + -1 + 6m

Combine like terms: 1 + -1 = 0
4m = 0 + 6m
4m = 6m

Solving
4m = 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
4m + -6m = 6m + -6m

Combine like terms: 4m + -6m = -2m
-2m = 6m + -6m

Combine like terms: 6m + -6m = 0
-2m = 0

Divide each side by '-2'.
m = 0

Simplifying
m = 0

See similar equations:

| 3e(3e-10)=2 | | 9x(x+2y+3z)= | | 6s^3+23s^2+33s=13s | | 3x-5=5+3x | | y+x^2-2x=0 | | x+y^2-2y=0 | | 10y+5x=100 | | 4y-24-9y+31= | | -4(y-3)=6y-38 | | f(-2)=-2+2(-2-1) | | -9x+-18+25=-38 | | 3+(-22)= | | 7-11x=x-33 | | 3log(7)(4)-5log(7)(m)= | | f(3)=3+2(3-1) | | -2x-10=44+8x | | 5t-2t=t | | 2z^2+7x=0 | | -4(2-y)+3y=4(y-4) | | (2x+4)(x-3)=0 | | f(-2)=-3(4-2)+2 | | 2x-3=4y+6 | | 4x^2-6x+5=x+1 | | 210x+100-72x^2=0 | | -9+4-(-5)= | | 8-3a^3=0 | | f(3)=-3(4-3)+2 | | X-6+2x=48 | | 64=-3(1-2n) | | 2x^2+28x+74=0 | | -65=136 | | 9z^2-26z-3=0 |

Equations solver categories